Experimental Goettingen minipig and beagle dog as two species used in bioequivalence studies for clinical pharmacology (5-aminosalicylic acid and atenolol as model drugs) - Kvetina, J; Svoboda, Z; Nobilis, M; Pastera, J; Anzenbacher, P (General physiology and biophysics, 1999)
Due to proven similarities in biotransformation between man and minipig, minipig seems to be the experimental animal of choice for preclinical pharmacokinetic studies when an experiment with a drug exhibiting a great first pass bioelimination (like 5-aminosalicylic acid) is to be realised. On the other hand, both minipig and dog may be suitable species for a pharmacokinetic study with a drug characterized by a small extent of first pass biotransformation (like atenolol).
Keywords: Swine, Miniature; psi; mesalamin; Dogs; plocha pod křivkou; Chromatography, High Pressure Liquid; atenolol; vysokoúčinná kapalinová chromatografie; miniaturní prasata; terapeutická ekvivalence; Therapeutic Equivalency; biotransformace; Biotransformation; Swine; Atenolol; zvířata; Humans; Mesalamine; Area Under Curve; prasata; lidé; Animals